2017
DOI: 10.1364/oe.25.015581
|View full text |Cite
|
Sign up to set email alerts
|

High quality chalcogenide-silica hybrid wedge resonator

Abstract: Chalcogenide glasses, with high nonlinearity and low loss, have captured research interest as an integrated device platform for near- and mid-infrared nonlinear optical devices. Compared to silicon-based microfabrication technologies, chalcogenide fabrication processes are less mature and a major challenge is obtaining high quality devices. In this paper, we report a hybrid resonator design leveraging a high quality silica resonator to achieve high Q factors with chalcogenide. The device is composed of a thin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…1. It is possible that a higher overlap integral could be realized using a different resonator geometry that confines the standing acoustic wave more tightly (possibly a wedge or disc resonator [34]), leading to Brillouin combs of higher optical power. It has also been reported that the Brillouin gain can be enhanced in sub-wavelength waveguides where the radiation pressure at the air-waveguide interface dominate the electrostrictive forces [35,36].…”
Section: Resultsmentioning
confidence: 99%
“…1. It is possible that a higher overlap integral could be realized using a different resonator geometry that confines the standing acoustic wave more tightly (possibly a wedge or disc resonator [34]), leading to Brillouin combs of higher optical power. It has also been reported that the Brillouin gain can be enhanced in sub-wavelength waveguides where the radiation pressure at the air-waveguide interface dominate the electrostrictive forces [35,36].…”
Section: Resultsmentioning
confidence: 99%
“…However, their inherent irregular nanostructure related to variations of stoichiometry and bond structures tends to result in a characteristic nanoscale roughness when etched due to nonuniformity in the local etch rate 18 . Over the past decade, there have been pioneering works to address this issue by optimizing direct etching 19,20 or introducing indirect pattering methods 21,22 . Nevertheless, the loss of on-chip chalcogenide devices has lagged far behind that of chalcogenide optical fiber 17 , micro-sphere 23,24 , or theoretical estimations 25 .…”
Section: Resultsmentioning
confidence: 99%
“…Starting with a silica-on-silicon wafer, photolithography (HMDS followed by AZ GXR601 photoresist) and resist reflow (140 °C for 40 min) are used to define the SiO 2 microdisk pattern. A buffered oxide etch (6:1 BOE, 0.37 μm/s etch rate, deionized water rinse) transfers the photoresist pattern into the silica layer, creating a wedged microdisk cross-section . After removing the photoresist using acetone and isopropyl alcohol, a hydrofluoric, nitric and acetic acid (HNA) wet etch (HF: 10 mL; HNO 3 : 120 mL; CH 3 COOH: 100 mL; 15 min at 25 °C) is used to selectively remove the underlying silicon layer, resulting in an undercut SiO 2 microdisk supported by a silicon pedestal.…”
mentioning
confidence: 99%